Peran Rumah Yatim dan Tahfiz Ulul Al-Bab dalam Pendidikan Islam pada Anak-Anak dan Remaja - Kirana (STAI Ihyaul Ulum Gresik, 2023)
The Role of Orphanages and Tahfiz Ulul Al-Bab in Islamic Education for Children and Youth in Mentibar Village, which is in Paloh District, Sambas Regency. This research departs from the phenomenon of child and adolescent delinquency in general, one of the challenges of educational institutions for families and schools in Mentibar has also established educational institutions for orphans or for children who cannot afford the purpose of which is to improve or foster morals, behavior children andyouth and also to provide provision of religious knowledge. The focus of this research are: 1) How is the Orphanage House and Tahfiz Ulul Al-Bab education program in Islamic education for children and adolescents in Mentibar Village, Paloh District? 2) What is the view of the people of Mentibar Village on the establishment of the Orphanage and Tahfiz Ulul Al-Bab House in Mentibar Village, Paloh District? 3) Why do parents include their orphans and Tahfiz Ulul Al-Bab in Mentibar Village, Paloh District?This study uses a qualitative approach and the method used is descriptive method, meaning that research is intended to describe, describe, or describe the condition of the object under study as it is, in accordance with the circumstances when the research was carried out. Based on the results of research on the Role of Orphanages and Tahfiz Ulul Al- Bab in Islamic Education for Children and Youth in Mentibar Village, Paloh District, in general they include: 1) Orphanage Home Education Program and Tahfiz Ulul Al-Bab in Islamic Education in Mentibar Village Paloh sub-district: Al-Qur'an memorization program, echo (Qur'an reading movement), tadarusan at the nearest mosque and surau, I'tikaf, Friday safari, visits or comparative studies to other institutions, there are also gardening and raising goats. 2) Views of the Mentibar Village Community on the Establishment of Orphanages and Tahfiz Ulul Al-Bab in Mentibar Village, Paloh District: Parents really feel helped in guiding and fostering their children so that they are not influenced by the outside world which has many negative impacts with the existence of this institution. parents are not worried because they do more useful activities as long as they are at the Orphan and Tahfiz Ulul Al-Bab institution in Mentibar Village. 3) Reasons for Parents Sending Their Children to Orphan Houses and Tahfiz Ulul Al-Bab in Mentibar Village, Paloh District: The reason for sending their children is so that their children learn more about Islam, increase their memorization of the Qur'an, change their morals children so that they are better, and train children to be independent and reduce children's activities in playing mobile phones.